2021
DOI: 10.5888/pcd18.200352
|View full text |Cite
|
Sign up to set email alerts
|

Rural, Suburban, and Urban Differences in Chronic Pain and Coping Among Adults in North Carolina: 2018 Behavioral Risk Factor Surveillance System

Abstract: Introduction Our study aimed to examine the prevalence of chronic pain, its severity, its causes, and coping mechanisms that are used by North Carolina adults in rural, suburban, and urban areas. Methods We analyzed data from the Behavioral Risk Factor Surveillance System’s first chronic pain module in 2018, representing 3,598 respondents. Self-reported chronic pain was defined as the affirmative response to the question, “Do you suffer from any type of chronic pain, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Overall, an issue that has become important in the modern healthcare system is the rural health. Rural and urban social environments differ so much that studies should not generalize findings across these populations [ 10 , 11 ]. Specifically, some previous research indicated that rural populations are unique in culture, economics, lifestyle, values, population mix, social organization, and behaviors relating to illness and healthcare [ 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, an issue that has become important in the modern healthcare system is the rural health. Rural and urban social environments differ so much that studies should not generalize findings across these populations [ 10 , 11 ]. Specifically, some previous research indicated that rural populations are unique in culture, economics, lifestyle, values, population mix, social organization, and behaviors relating to illness and healthcare [ 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study based on the US National Survey of American Life found that rural African American women had overall worse health than their urban counterparts [ 22 ]. Additionally, rural residents in North Carolina were more likely to have chronic pain than their urban counterparts [ 23 ].…”
Section: Introductionmentioning
confidence: 99%